Acid-catalyzed intramolecular cyclization of N-(4, 4-diethoxybutyl)sulfonamides as a novel approach to the 1-sulfonyl-2-arylpyrrolidines. Issue 1 (2nd January 2017) - Gazizov, Almir S.; Smolobochkin, Andrey V.; Anikina, Ekaterina A.; Voronina, Julia K.; Burilov, Alexander R.; Pudovik, Michail A.
ABSTRACT: Herein we report our studies on the acid-catalyzed cyclisation of N-(4, 4-diethoxybutyl)sulfonamides at the presence of polyatomic phenols as an efficient one-pot approach to the synthesis of 1-sulfonyl-2-arylpyrrolidines from the acyclic precursors. GRAPHICAL ABSTRACT: